Penerapan algoritma Shortest Job First ( SJF) dan Priority Scheduling (PS) Pada Maintanance Mesin ATM - Sundari, Siti; Syahputra, M Yogie; Rismayanti, Rismayanti (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2023)
In the banking world there are scheduling problems and is one of the important aspects for the smooth operation of the company, especially in the ATM (automatic teller machine). There is no initial system in scheduling repairs and charging money a cash machine so it is necessary to run the company's operations well. In this study wanted to propose a scheduling system that uses two algorithms that can be used as a comparison in scheduling. Algorithms that can be implemented in a queue system, one of which is SJF (Shortest Job First) and Priority Scheduling. The existence of applications with this system, users can know the schedule of preventive maintenance so as to facilitate the division of operation maintenance in the company in carrying out their respective duties. Key Words: ATM(automatic teller machine), Shortest Job First, Priority Scheduling